Practical challenges of continuous real-time functional magnetic resonance imaging neurofeedback with multiband accelerated echo-planar imaging and short repetition times - Renz, Malika; Zidda, Francesca; Andoh, Jamila; Prager, Marcel; Sack, Markus; Becker, Robert; Ruf, Matthias; Schmitgen, Mike; Wolf, Robert Christian; Meyer-Lindenberg, Andreas; Tost, Heike (Human brain mapping, 2023)
Continuous real-time functional magnetic resonance imaging (fMRI) neurofeedback is gaining increasing scientific attention in clinical neuroscience and may benefit from the short repetition times of modern multiband echoplanar imaging sequences. However, minimizing feedback delay can result in technical challenges. Here, we report a technical problem we experienced during continuous fMRI neurofeedback with multiband echoplanar imaging and short repetition times. We identify the possible origins of this problem, describe our current interim solution and provide openly available workflows and code to other researchers in case they wish to use a similar approach.